2017
DOI: 10.1186/s40413-017-0162-3
|View full text |Cite
|
Sign up to set email alerts
|

Debates in allergy medicine: Molecular allergy diagnosis with ISAC will replace screenings by skin prick test in the future

Abstract: In today’s clinical practice patients’ skin is used as screening organ for diagnosing type 1 allergy. According to European guidelines skin prick testing with a panel of 18 allergen extracts is recommended, in the US between 10 to 50 allergens are used. The specificity and sensitivity of skin testing is individually highly variable depending on age, body mass, and skin barrier status. In atopic inflammation skin testing gives more false positive results. Smaller skin area and strain limits prick testing in sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 55 publications
0
29
0
3
Order By: Relevance
“…49 Equally important is the fact that clinically relevant sensitizations can be differentiated from non-relevant sensitizations to CCDs and profilins, which translate to practical, relevant recommendations for patients. 121,122 Along these lines, it has been observed that co-sensitization to profilins is associated with a lower occurrence of systemic reactions to nsLTP or storage proteins. 123…”
Section: Pamd@ In Selected Sensitizations Respiratory Allergensmentioning
confidence: 99%
See 1 more Smart Citation
“…49 Equally important is the fact that clinically relevant sensitizations can be differentiated from non-relevant sensitizations to CCDs and profilins, which translate to practical, relevant recommendations for patients. 121,122 Along these lines, it has been observed that co-sensitization to profilins is associated with a lower occurrence of systemic reactions to nsLTP or storage proteins. 123…”
Section: Pamd@ In Selected Sensitizations Respiratory Allergensmentioning
confidence: 99%
“…However, considering the risk of in vivo tests for diagnosing patients with a previous systemic reaction, multiplex IgE testing is an interesting alternative tool to examine the IgE profile and level of sensitization in a semiquantitative manner in settings when SPT cannot be applied. 122 Of course, cofactors cannot be considered or predicted. Likely, clustering algorithms like those recently developed for allergic rhinitis and asthma 116 are needed for improving the accuracy of risk evaluation in food allergy by PAMD@, but overall, clinical studies on multiplex IgE testing indicate good reliability for risk assessment.…”
Section: Food Allergensmentioning
confidence: 99%
“…Molecular allergy diagnosis has entered clinical practice in humans, allowing either approaches “from clinics to molecules” or “from molecules to clinics” . It is debated whether it might replace skin testing screenings in the future, or not …”
Section: Introductionmentioning
confidence: 99%
“…Estudios han demostrado que en 50 % puede estarse indicando erróneamente ITSL o ITSC cuando esta se basa en el resultado de la PCP. 31 El diagnóstico molecular de alergia con alérgenos simples o micromatrices de alergia múltiple es un ejemplo típico de la medicina de precisión 21,32 que mejora la especificidad del diagnóstico de sensibilización a aeroalérgenos; especialmente en pacientes polisensibles, se puede aplicar en las alergias alimentarias e, incluso, puede revelar anafilaxia inexplicada. 33 1.2.7.…”
Section: Prueba De Activación De Basófilos (Bat) En El Diagnóstico Deunclassified
“…Por ello, las pruebas in vitro, que primero surgieron como pruebas alternativas para pacientes que no podían ser sometidos a PCP, cada vez están cobrando un lugar de mayor importancia en el abordaje diagnóstico integral del paciente alérgico. 21 En el paciente que muestre polisensibilización el diagnóstico molecular en suero, la PCP podría orientar hacia la presencia de panalérgenos y al ajuste en los extractos a elegir para la ITA; de igual manera, en los pacientes con historia clínica positiva para alergia a veneno de himenópteros, pero con resultados ambiguos en pruebas cutáneas que podrían indicar alergia a varios véspidos, el diagnóstico molecular podría ser de utilidad.…”
Section: Introductionunclassified